Additions to the knowledge of fungi poliporoides of Chiapas - Medina-Jaritz, Nora B.; Palacios-Pacheco, Mauricio R.; Valenzuela-Garza, Ricardo (Instituto de Ecología, A.C., 2022)
We report 24 polypore species belonging to five families. This study is based on 93 specimens collected in the rain forest that surrounds the archeological zone of Yaxchilán, Chiapas. We made descriptions in accordance with the guidelines of modern taxonomy.